Experimental Perspectives on Presuppositions
VIII, 262 p. 58 illus.
Keywords: This volume brings together some of the most recent developments in the field of experimental pragmatics, specifically empirical approaches to theoretical issues in presupposition theory. It includes studies of the online processing of presupposed content; investigations of the interpretive properties of presuppositions in various linguistic contexts; comparative perspectives relative to other aspects of meaning, such as asserted content and implicatures; cross-linguistic comparisons of presupposition triggers; and perspectives from language acquisition. Taken together, these novel contributions provide a snapshot of state-of-the art developments in this area and will serve as a point of reference for numerous emerging avenues of future work. It makes for an ideal set of readings for advanced university courses on experimental studies of meaning and is a must-read for anyone interested in experimental research on meaning in natural language.